Ghana : Poverty Reduction Strategy Paper Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2004)
The Poverty Reduction Strategy Paper Annual Progress Report (PRSPs) on Ghana explains macroeconomic, structural, and social policies in support of growth and poverty reduction, as well as associated external financing needs and major sources of financing. The Annual Progress Report (APR) provides a framework for the systematic review of the Ghana Poverty Reduction Strategy (GPRS) programs and projects implementation and their impacts on the socioeconomic development of the country. Given the significant resources required to fund the GPRS, the government has prioritized the GPRS through the Medium-Term Priorities (MTPs), which have been used to inform the budget.